A survey of the opinions of the Secretary of Justice on legal issues in education, 1940-1975 - Cutaran, Patrocinio L. Francisco 1935- (1976)
Analysis of primary sources from 1940 to 1975 looked into the basis of the power of the Secretary of Justice to render legal advisory opinions and to identify legal issues in education. Most of the issues brought to the Secretary were initiated by the top echelon rather than the lower echelon of the educational system. Among the issues, administration and supervision ranked first, perhaps because administrative problems affect individual rights as well as the public welfare. Majority of the issues regarding curriculum and instruction seeking to depart from standards set by law or by the National Board of Education were generally answered in the negative. The institutions seeking exemption tend to consider themselves independent of genaral laws.
Mimeographed.
Thesis (M.Ed.)--University of the Philippines, Quezon City
Vita
Keywords: Philippines. Dept. of Justice; Educational law and legislation -- Philippines